2018
DOI: 10.1002/pssb.201800477
|View full text |Cite
|
Sign up to set email alerts
|

3D GaN Fins as a Versatile Platform for a‐Plane‐Based Devices

Abstract: GaN fins on GaN-on-sapphire templates are fabricated by continuous mode selective area metalorganic vapor phase epitaxy. The fins exhibit high aspect ratios and smooth nonpolar aplane sidewalls with an ultra-low threading dislocation density of a few 10 5 cm -2 making them ideally suited for optoelectronic to electronic applications. A detailed analysis of the inner structure of GaN fins is provided by the help of marker layer experiments and correlation of results from fins fabricated under different growth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The dark-spot contrast can be used to estimate the dislocation density on the fin sidewalls. 25 Averaging over several fins, a dislocation density of (6 ± 3) × 10 7 cm −2 is obtained for the AlGaN fins with an aluminum content of around 30% investigated in this study. This is a remarkably low value compared to that of conventional heteroepitaxial AlN-on-sapphire templates, which generally exceeds a threading dislocation density of 10 9 cm −2 .…”
Section: ■ Results and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The dark-spot contrast can be used to estimate the dislocation density on the fin sidewalls. 25 Averaging over several fins, a dislocation density of (6 ± 3) × 10 7 cm −2 is obtained for the AlGaN fins with an aluminum content of around 30% investigated in this study. This is a remarkably low value compared to that of conventional heteroepitaxial AlN-on-sapphire templates, which generally exceeds a threading dislocation density of 10 9 cm −2 .…”
Section: ■ Results and Discussionmentioning
confidence: 64%
“…23,24 The properties of GaN microfins have been discussed by Hartmann et al, and dislocation densities on the nonpolar a-plane sidewalls as low as (3 ± 2) × 10 5 cm −2 have been demonstrated. 25 A universal challenge for the approach of GaN/AlGaN core−shell microstructures that other researchers and our group have struggled with is the mitigation of cracking of the AlGaN shell layers which grow under increasingly tensile strain as the aluminum content is raised. 26,27 In our case, the use of a graded short-period superlattice (SPSL) allows for the growth of a mostly crackfree AlGaN shell that presents itself as an appropriate template for the growth of nonpolar a-plane AlGaN QWs emitting at the intersection of the UV-A and UV-B spectral regions (further information can be found in Supporting Information S1).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The fabrication process started with etching the GaN film to generate a fin structure by reactive ion etching (RIE) with a Ni mask layer, which was photolithographically patterned by the step and repeat projection aligner for the submicrometer‐sized fins. Recent research showed the availability of the bottom‐up growth of a fin using selective area metal–organic vapor phase epitaxy . Afterward, tetramethylammonium hydroxide (TMAH) treatment at 85 °C for 50 min was used in this structure to make the sidewall of the fin smoother, as shown in Figure b .…”
Section: Methodsmentioning
confidence: 99%
“…Metal-Organic Vapor Phase Epitaxy (MOVPE) is one of the most popular deposition methods used in the mass production of compound semiconductors, especially the III-V group compounds, such as gallium nitride (GaN) or gallium arsenide (GaAs). This technique has gained popularity over the past few decades due to rapid amount of development-especially in the field of optoelectronics and power electronic devicesbased on these semiconductor materials [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%